2019
DOI: 10.3390/polym11111769
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Thermo-Mechanical and Antimicrobial Properties of DBD Plasma Treated Disinfectant-Impregnated Wipes during Storage

Abstract: Disinfectant-impregnated wipes are broadly used in hospitals, as an important approach for infection prevention and control. But their ageing performance has rarely been studied. Untreated and Dielectric Barrier Discharge (DBD) plasma pre-treated wiping materials made of nonwoven 100% polyester (W1), nonwoven 55% cellulose/45% polyester (W2) and woven cotton (W3) were impregnated with a quaternary ammonium compound solution (ADBAC) for 30 min, 3, 7, 15, and 30 days of storage time and characterized in term of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
3
4
0
Order By: Relevance
“…With time, the values approach the angle measured before being treated, emphasizing the aging process. This result confirms what has already been reported for other studies that modified polymeric materials by plasma at low pressure or atmospheric pressure [ 3 , 9 , 16 , 42 , 59 , 66 , 67 ]. Because the bonds generated by plasma treatment are formed only on the HDPE surface, the mobility of the polymeric chain and reaction of these polar groups with the environment humidity can promote the breakage of this bond or the stabilization of the same [ 3 , 9 , 16 , 42 , 66 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…With time, the values approach the angle measured before being treated, emphasizing the aging process. This result confirms what has already been reported for other studies that modified polymeric materials by plasma at low pressure or atmospheric pressure [ 3 , 9 , 16 , 42 , 59 , 66 , 67 ]. Because the bonds generated by plasma treatment are formed only on the HDPE surface, the mobility of the polymeric chain and reaction of these polar groups with the environment humidity can promote the breakage of this bond or the stabilization of the same [ 3 , 9 , 16 , 42 , 66 ].…”
Section: Resultssupporting
confidence: 92%
“…Since the chemical modifications have aged over time, influencing the polar coordinate more clearly, due to the formation of functional groups with oxygen, the physical modification tends to be maintained, with the aging of morphological modifications not evident in polymers [ 1 , 33 ]. This change in surface roughness is due to the etching action promoted by the species present in the plasma, as reported in the literature [ 67 , 72 , 73 , 74 , 75 ].…”
Section: Resultssupporting
confidence: 60%
“…It seems that the antimicrobial test result did not show a significant increase from the plasma-treated wipe samples even though a higher ADBAC concentration was observed from the XPS analysis. However, in a previous aging study of the plasma effect on antimicrobial efficacy, it was found that plasma treatment can prolong the release of increased ADBAC on the surface of W1 (polyester) doubling the shelf time . This result, in addition to the fact that only in the pure polyester wipe (W1) was it possible to observe a significant amount of ADBAC on the wipe surface, demonstrates the efficacy of plasma treatment in tightly maintaining the disinfectant where it is really needed for a long time.…”
Section: Resultsmentioning
confidence: 93%
“…They also said that the band at 2900 cm-1 indicated cellulose. Some other authors [43][44][45] explained the use of FTIR in the EVALUATION OF GUAR GUM FOR THE CONSOLIDATION OF SOME CELLULOSIC .. __________________________________________________________________________________________________________________ ________________________________________________ Egypt. J. Chem.…”
Section: Fig 2 Ftir-atr Analysis Of Treated Linen Samples Withmentioning
confidence: 99%